In situ observations of fullerene fusion and ejection in carbon nanotubes. - Gorantla, S; Börrnert, F; Bachmatiuk, A; Dimitrakopoulou, M; Schönfelder, R; Schäffel, F; Thomas, J; Gemming, T; Borowiak-Palen, E; Warner, J; Yakobson, B; Eckert, J; et al. (2010)
We present in situ experimental observations of fullerenes seamlessly fusing to single-walled carbon nanotubes. The morphing-entry of a fullerene to the interior of a nanotube is also captured. The confined (1D) motion of the newly-encapsulated fullerene within its host attests to the actual change from the exterior to interior.